2022
DOI: 10.3390/molecules27031147
|View full text |Cite
|
Sign up to set email alerts
|

Alpha B-Crystallin in Muscle Disease Prevention: The Role of Physical Activity

Abstract: HSPB5 or alpha B-crystallin (CRYAB), originally identified as lens protein, is one of the most widespread and represented of the human small heat shock proteins (sHSPs). It is greatly expressed in tissue with high rates of oxidative metabolism, such as skeletal and cardiac muscles, where HSPB5 dysfunction is associated with a plethora of human diseases. Since HSPB5 has a major role in protecting muscle tissues from the alterations of protein stability (i.e., microfilaments, microtubules, and intermediate filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 188 publications
0
9
0
Order By: Relevance
“…The increased mRNA expression of an alpha isoform ( CAMK2A ) of this protein in WS meat was reported previously ( Marchesi et al, 2019 ), indicating calcium dyshomeostatic conditions observed in chicken breast myopathies including WS meat ( Zhang et al, 2023 ). CRYAB is a member of the small heat shock protein family which functions as a molecular chaperone ( Dimauro and Caporossi, 2022 ). Earlier studies showed increased mRNA expression of CRYAB in chicken breast myopathies ( Zambonelli et al, 2016 ; Pampouille et al, 2019 ), which is consistent with higher abundance in WS meat in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased mRNA expression of an alpha isoform ( CAMK2A ) of this protein in WS meat was reported previously ( Marchesi et al, 2019 ), indicating calcium dyshomeostatic conditions observed in chicken breast myopathies including WS meat ( Zhang et al, 2023 ). CRYAB is a member of the small heat shock protein family which functions as a molecular chaperone ( Dimauro and Caporossi, 2022 ). Earlier studies showed increased mRNA expression of CRYAB in chicken breast myopathies ( Zambonelli et al, 2016 ; Pampouille et al, 2019 ), which is consistent with higher abundance in WS meat in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies showed increased mRNA expression of CRYAB in chicken breast myopathies ( Zambonelli et al, 2016 ; Pampouille et al, 2019 ), which is consistent with higher abundance in WS meat in this study. CRYAB exhibits diverse functions in skeletal muscles including protecting muscle tissues from alterations of protein stabilities in structuring microfilaments, microtubules, and intermediate filament components ( Dimauro and Caporossi, 2022 ). Therefore, greater abundance of CRYAB in WS meat may affect meat/texture quality in addition to being a marker of inducing chicken breast myopathies including WS.…”
Section: Resultsmentioning
confidence: 99%
“…Since HSPB5 has been suggested to function as a chaperone for denatured proteins under ER stress ( Figure 6 b) [ 35 , 36 ], we further examined the inhibitory effect of recombinant HSPB5 on ER stress-induced caspase 3 activity. Overexpression of HSPB5 (WT) significantly suppressed ER stress-induced caspase 3 activity after MG132 treatment ( Figure 7 d).…”
Section: Resultsmentioning
confidence: 99%
“…PLK2 belongs to the polo-like kinase family and has recently been investigated as a therapeutic target for tumors [ 24 ]. We further showed that PLK2 phosphorylates serine 19, one of the three phosphorylation sites of HSPB5 [ 35 , 40 ], suppresses apoptosis induced by MG132-induced ER stress. Our findings provide new insights into cytoprotection by the PLK2/HSPB5 pathway in ER stress-induced cell apoptosis ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The human HSPB5 gene (CRYAB), located on chromosome 11q23, encodes αB-crystallin a 175 amino acid protein with a molecular mass of 20 kDa [49]. The protein, which is highly expressed in tissues with elevated rates of oxidative metabolism, including cardiac and skeletal muscle, consists of a conserved central domain called the "α-crystallin domain" (60-150 aa), the flanking N-terminal region, and the C-terminal region [50][51][52]. In adult skeletal muscle, αB-crystallin, a small heat shock protein (HSP) that acts as a molecular chaperone binding misfolded and denatured proteins to prevent their aggregation, is located at the level of the Z-disk and is associated with actin and titin [52,53].…”
Section: Discussionmentioning
confidence: 99%